Short-Term Effects of a Multidimensional Stress Prevention Program on Quality of Life, Well-Being and Psychological Resources. A Randomized Controlled Trial - Recabarren, Romina Evelyn; Gaillard, Claudie; Guillod, Matthias; Martin-Soelch, Chantal (Frontiers in Psychiatry, 2019)
It is well-documented that university students have an increased risk in developing psychological problems because they face multiple stressors. Cognitive, behavioral, and mindfulness-based stress prevention programs were shown to reduce symptoms of anxiety, depression, and perceived stress in university students. However, little is known of their effect on resource activation. Additionally, most validated interventions are unidimensional, i.e. including one stress-coping approach. In this study, we investigated the short-term effects of a multidimensional stress prevention program on students’ quality of life, psychological symptoms and resources, and resilience factors against stress. Using an experimental design, 64 healthy undergraduate students (56 women), between 18 and 34 years old (M = 21.34, SD = 2.53), from the University of Fribourg, Switzerland, were randomly allocated either to the intervention or the wait-list control group. The intervention group participated in a multidimensional stress prevention program, integrating mindfulness-based activities, cognitive and behavioral strategies, social skills, and emotional regulation exercises. The program consisted of eight two-hour weekly sessions. Before and after the intervention, participants completed self-reported questionnaires evaluating quality of life; psychological symptoms such as depression, anxiety, social anxiety, and interpersonal problems; as well as psychological resources like self-efficacy, sense of coherence, self-compassion, and social support, presented online. A standardized clinical interview was performed at pre- and post-measurement times. To analyze the sort-term effects of the program, we used mixed, two-factorial ANOVAs (per-protocol analyses). In accordance with our hypotheses, our results showed significant reduction of psychological symptoms, including anxiety, interpersonal problems, and symptoms of pain; a significant increase in quality of life, sense of coherence, and self-compassion in students who participated in the intervention program compared to the control group, (all p values < .05). No significant results were found for symptoms of depression, social anxiety, self-efficacy, and social support. These preliminary findings indicate specific short-term effects of our multidimensional stress prevention program on psychological symptoms and on quality of life as well as promising effects on psychological resources and factors associated with resilience against stress. Future studies should investigate the long-term effects of the intervention as well as the effects in clinical samples.